Inconsistencies Between the Digital RDTR and Building Permits (PBG): Legal Analysis of Implementation Conflicts in the OSS-RBA System After the Enactment of UU Cipta Kerja - Izzati, Hafizah Nurul; Gibran, Raihan Maulana; Fawazy, Ashar; Hafizah, Desi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The implementation of the OSS-RBA system following the enactment of UU Cipta Kerja was intended to simplify and accelerate business licensing in Indonesia. However, the issuance of Building Approval Permits (PBG) through OSS-RBA often conflicts with the Digital Detailed Spatial Plan (RDTR), which should function as the main instrument of spatial control. This study aims to analyze the legal relationship between digital RDTR and PBG issuance, identify the causes of inconsistency, and formulate an integration model to ensure legal certainty. This research uses a normative legal method with statutory and conceptual approaches. Legal materials consist of legislation, books, journals, and related references, analyzed descriptively. The results show that RDTR remains the primary legal basis for determining spatial conformity, while PBG must comply with spatial planning rules and technical building standards. Inconsistencies occur due to limited digital RDTR availability, regulatory disharmony, overlapping authority between central and regional governments, and weak coordination. These conditions may cause PBG to be administratively valid but problematic in spatial terms. Therefore, stronger integration between RDTR and OSS-RBA is required through data synchronization, regulatory harmonization, stronger regional verification, and effective supervision. This is necessary to ensure efficient licensing, legal certainty, and good governance.